The Good, the Bad, and the Missed Boom - Perotti, Enrico; Rola-Janicka, Magdalena (Review of Financial Studies, 2022)
Abstract Some credit booms result in financial crises. While excessive risk-taking could plausibly explain the boom-to-bust cycle, many investors do not anticipate increasing risk. We show that credit booms may be misunderstood as being driven by high productivity because opaque bank assets disguise risk incentives. Balanced funding relative to productive prospects can sustain prudent lending (good boom), whereas funding imbalances may induce high risk exposure and boost asset prices (bad boom) or lead to asset underpricing and insufficient lending (missed boom). Rational agents drawing inference from prices make mistakes that can amplify the effect of funding imbalances and propagate risk. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.